PENGEMBANGAN MEDIA MIBI TEMA INDAHNYA KEBERSAMAAN KELAS IV SD - Arief Hidayat Afendi; Yessi Fatima Hutasuhut; Dinda Yharsal (Jurnal PGSD, 2022)
ABSTRACT MIBI Media Development Theme for the Beauty of Togetherness for Class IV Elementary School. This thesis discusses the Development of MIBI (Miniature Indonesian Culture) Learning Media The Theme of the Beauty of Togetherness for class IV SD 066667 Medan Denai. The development model used in this study uses research and development (R & D) methods with the ADDIE development model developed by Reiser and Molenda. The steps used in this study include (Analysis-Design-Development-Implement-Evaluate). The source of the data for this research is the fourth grade students of SD 066667. The data collection technique used is using a questionnaire. The validation of the development of this learning media involves 2 validators, namely material experts and media experts. Based on the results of the study, the results of the validation of material experts obtained percentage data of 90.90% in the "very valid" category, and the results of the validation of media design experts with a percentage of 97.36% in the "very valid" category, as well as the validation results from the use trial. with a percentage of 94.11% with the "very valid" category from the acquisition, it means that the MIBI (Miniature Indonesian Culture) learning media is very suitable for use in thematic learning. Keyword: MIBI Media Development, Thematic Learning. ABSTRAK Pengembangan Media MIBI Tema Indahnya Kebersamaan Kelas IV SD. Skripsi ini membahas tentang Pengemangan Media Pembelajaran MIBI (Miniatur Budaya Indonesia) Tema Indahnya Kebersamaan kelas IV SD 066667 Medan Denai. Model pengembangan yang digunakan dalam penelitian ini menggunakan metode penelitian dan pengembangan (Research and Development/ R & D) dengan model pengembangan ADDIE yang dikembangkan oleh Reiser dan Molenda. Langkah yang digunakan dalam penelitian ini meliputi (Analysis-Design-Development-Implement-Evaluate). Sumber data penelitian ini adalah siswa kelas IV SD 066667 Teknik pengumpulan data yang digunakan yaitu menggunakan angket. Validasi pengembangan media pembelajaran ini melibatkan 2 validator yaitu ahli materi, dan ahli media. Berdasarkan hasil penelitian, hasil validasi ahli materi memperoleh data persentase sebesar 90,90% dengan kategori “sangat valid”, dan hasil validasi ahli desain media dengan presentase sebesar 97,36% dengan kategori “sangat valid”, serta hasil validasi dari uji coba pemakaian dengan presentase 94,11% dengan kategori “sangat valid” dari perolehan tersebut artinya media pembelajaran MIBI (Miniatur Budaya Indonesia) ini sangat layak untuk digunakan pada pembelajaran Tematik. Kata Kunci: Pengembangan Media MIBI, Pembelajaran Tematik.